Edge‐Epitaxial Growth of InSe Nanowires toward High‐Performance Photodetectors. Issue 4 (22nd December 2019) - Hao, Song; Yan, Shengnan; Wang, Yang; Xu, Tao; Zhang, Hui; Cong, Xin; Li, Lingfei; Liu, Xiaowei; Cao, Tianjun; Gao, Anyuan; Zhang, Lili; Jia, Lanxin; et al.
Abstract: Semiconducting nanowires offer many opportunities for electronic and optoelectronic device applications due to their unique geometries and physical properties. However, it is challenging to synthesize semiconducting nanowires directly on a SiO2 /Si substrate due to lattice mismatch. Here, a catalysis‐free approach is developed to achieve direct synthesis of long and straight InSe nanowires on SiO2 /Si substrates through edge‐homoepitaxial growth. Parallel InSe nanowires are achieved further on SiO2 /Si substrates through controlling growth conditions. The underlying growth mechanism is attributed to a selenium self‐driven vapor–liquid–solid process, which is distinct from the conventional metal‐catalytic vapor–liquid–solid method widely used for growing Si and III–V nanowires. Furthermore, it is demonstrated that the as‐grown InSe nanowire‐based visible light photodetector simultaneously possesses an extraordinary photoresponsivity of 271 A W −1, ultrahigh detectivity of 1.57 × 10 14 Jones, and a fast response speed of microsecond scale. The excellent performance of the photodetector indicates that as‐grown InSe nanowires are promising in future optoelectronic applications. More importantly, the proposed edge‐homoepitaxial approach may open up a novel avenue for direct synthesis of semiconducting nanowire arrays on SiO2 /Si substrates. Abstract : A catalysis‐free approach is developed for direct synthesis of long and straight InSe nanowires on SiO2 /Si substrates through edge‐homoepitaxial growth. The underlying growth mechanism is ascribed to selenium self‐driven vapor–liquid–solid processes, which is distinct from the conventional metal‐catalytic vapor–liquid–solid method widely used for growing Si and III–V nanowires. The InSe nanowire‐based visible light photodetector presents extraordinary photoresponsivity performance.